Proof LHS=RHS

Asked by shivamaihar25 | 3rd Jul, 2021, 10:33: PM

Expert Answer:

Let Matrix A = begin mathsize 14px style open square brackets table row 2 0 cell negative 1 end cell row 5 1 0 row 0 1 3 end table close square brackets end style  and Matrix B = begin mathsize 14px style open square brackets table row 3 cell negative 1 end cell 1 row cell negative 15 end cell 6 cell negative 5 end cell row 5 cell negative 2 end cell 2 end table close square brackets end style
If A-1 = B , then   A × B  = I  , where I is unit matrix of order 3 x 3 
 
BY matrix multiplication, it can be proved that product of matrix A and matrix B is unit matrix .
 
Hence , A-1 = B

Answered by Thiyagarajan K | 19th Sep, 2021, 12:43: AM